Komunikasi "Penyesuaian Diri Kembali" Pekerja Migran Perempuan yang Kembali ke Daerah Asal - Turnomo Rahardjo; Hapsari Dwiningtyas; Tandiyo Pradekso (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2018)
The problems of female migrant workers in foreign countries cannot be separated from the discourse of gender inequality. The social construction of women affects the working condition and employers’ treatment of female migrant workers while they are working abroad. The primary aim of this research is describing the re-entry process of female migrant workers when they return to their home country. The main theories used in this research are the U curve model and the W curve model. This research primarily related to the study of the cultural transition of minority groups (female migrant workers) by employing the phenomenology research method. The research finding shows a model of messaging strategies based on Curve W theory. The result also indicates that the social position of women and the cultural communication experiences of women migrant workers influence their capability in re-adapting. Emotional support from their significant others is essential to help the female migrant workers in going through the various stages of reentry cultural shocked so that they will be able to re-adapt. This study constructs a communication model that can be used as a guide for government agencies and NGOs working in helping female migrant workers who were experiencing reverse cultural shock. The communication models that emerge from this research are linear re-adaptation model, recovery model, and quitting model.